1995
DOI: 10.1111/j.1365-2095.1995.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spoilage and processing temperature on the quality of marine fish protein sources for salmonids

Abstract: Press cake meals were prepared from previously frozen herring immediately following thawing and after storage for 8 or 12 days at 2-5°C. Each of the raw sources of hemng was subjected to two processing temperatures, 75°C and 1OO"C, during meal preparation. Also, protein hydrolysates were prepared using ocean perch when fresh or after storage at 2-5°C for 4 or 8 days. Subsequently, each of the three hydrolysates was dried at 85°C or 93°C.In two separate experiments, each of the hemng press cake meals and dried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Nevertheless, some authors suggest that pH-stat is not a valid method for the measurement of protein digestibility, because differences in the buffering capacity of proteins could interfere with the measurement of protein hydrolysis. 24,25 In this sense the determination of baselines can be used as an indicator of such buffering capacity. 26,27 The baseline consumption of alkali was highly variable and, in some samples, considerable, amounting to up to 35% of the total uptake of alkali during the enzymatic digestion period.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some authors suggest that pH-stat is not a valid method for the measurement of protein digestibility, because differences in the buffering capacity of proteins could interfere with the measurement of protein hydrolysis. 24,25 In this sense the determination of baselines can be used as an indicator of such buffering capacity. 26,27 The baseline consumption of alkali was highly variable and, in some samples, considerable, amounting to up to 35% of the total uptake of alkali during the enzymatic digestion period.…”
Section: Discussionmentioning
confidence: 99%
“…(2002) reported the nutritional evaluation of selected by‐products including carp offal, fish frames from a number of marine species and trout offal. Clancy et al. (1995) made hydrolyzates from ocean perch stored for 0, 4 and 8 days and evaluated protein quality.…”
Section: Introductionmentioning
confidence: 99%
“…Gunasekera et al (2002) reported the nutritional evaluation of selected by-products including carp offal, fish frames from a number of marine species and trout offal. Clancy et al (1995) made hydrolyzates from ocean perch stored for 0, 4 and 8 days and evaluated protein quality. Digestibilities of fish processing by-products and fish meals have been reported by many investigators including feeding trials in trout and salmon by Sugiura et al (1998).…”
Section: Introductionmentioning
confidence: 99%
“…Various sources of fish meal are employed in marine shrimp diets because in general, they have high palatability and digestibility, excellent essential amino acid and fatty acid profiles, and high levels of available energy. However, fish meal quality may vary because of raw material spoilage and excessive Nutritive values of low and high fibre canola meals for shrimp (Penaeus vannamei) drying temperatures (> 100°C) during processing (McCallum & Higgs 1989;Pike et al 1990;Pike 1993;Clancy et al 1995). Also in some regions, the fish meal may contain different ratios of trash fish, small shrimp and other small aquatic animals (Penaflorida 1989).…”
Section: Introductionmentioning
confidence: 99%